1999
DOI: 10.1016/s0304-3959(99)00037-8
|View full text |Cite
|
Sign up to set email alerts
|

Plastic changes in sensory inputs to rat substantia gelatinosa neurons following peripheral inflammation

Abstract: Although hyperalgesia elicited by inflammation has been shown to be partly due to central sensitization, the cellular mechanisms are not clear at the moment. The present study was designed to address this issue using the blind whole-cell patch-clamp technique; glutamatergic primary-afferent inputs to substantia gelatinosa (SG) neurons were compared between spinal cord slices of naive rats and rats inflamed by an intraplantar injection of complete Freund's adjuvant. In naive rats, a large number of SG neurons e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
75
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 79 publications
(89 citation statements)
references
References 43 publications
12
75
2
Order By: Relevance
“…5C). Recording of the synaptic transmission between the C-fiber terminal and the secondorder neuron was carried out in lamina II, a translucent easily identified band in the superficial dorsal horn of spinal cord (38). We measured the miniature excitatory postsynaptic currents (mEPSCs) in the presence of tetrodotoxin (0.5 μM) and found that SNC80 and DAMGO reduced the frequency but not the amplitude of mEPSCs (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…5C). Recording of the synaptic transmission between the C-fiber terminal and the secondorder neuron was carried out in lamina II, a translucent easily identified band in the superficial dorsal horn of spinal cord (38). We measured the miniature excitatory postsynaptic currents (mEPSCs) in the presence of tetrodotoxin (0.5 μM) and found that SNC80 and DAMGO reduced the frequency but not the amplitude of mEPSCs (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In the spinal cord, synaptic transmission and sensory circuitry is shown to be unstable, changing easily the efficacy of synaptic transmission and termination of the inputs following pathological conditions (see Okamoto, 2000;Nakatsuka, 1999;Ito, 2000). Profound flexibility in the sensory system might be due to the primitivity of the system.…”
Section: Discussionmentioning
confidence: 99%
“…We have investigated the synaptic plasticity observed in various pathological conditions such as sciatic nerve transection (Okamoto, 2000), inflammation (Nakatsuka, 1999) and ovariectomy (OVX) (Ito, 2000). In this section some data are demonstrated to briefly show how the sensory transmission was modified by OVX using slice preparations from OVX rats.…”
Section: Synaptic Responses In the Spinal Cord Under Pathological Conmentioning
confidence: 99%
See 2 more Smart Citations